ONIX - upravljanje z nepremičninami - Ravnihar, Franc (Geodetski vestnik, 1998)
A brief outline of a GIS-supported real-estate management project is presented as one of three pilot sub-projects in the framework of the ONIX project. The paer focuses mainly on the completion of the preparatory phase, including a theoretical approach and modelling as the basis for implementation which is planned for the coming year
Keywords: geografski informacijski sistemi; nepremičnine; obdavčenje; projekt ONIX; upravljanje